Pengaruh Organizational Citizenship Behavior pada Performance dengan Service Quality, Satisfaction dan Behavior Intention Sebagai Anteseden - Suyono, Joko; Sunaryo, Sinto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
The purpose of the study is to observe the influence of organizational citizen behavior to performance. Organizational citizen behavior is affected by three variables namely satisfaction, service quality and behavior intention. The study was conducted on 12 nurses, 128 patients, and 10 nursing supervisor at a private hospital in Surakarta, Jawa Tengah. Stratified random sampling technique was applied to determine the number of sample. The result was based on structural equation modeling (SEM) method that showed there is no relationship between OCB and satisfaction and OCB to behavior intention. On the other hand, OCB to customer satisfaction, OCB to performance and satisfaction to performance are proved to be significant.